ANALISIS PENGGUNAAN GAYA BAHASA PADA PUISI – PUISI KARYA JOKO PINURBO DENGAN PENDEKATAN SEMIOTIK - Utin Maekatini Ayuningsih; Wikanengsih Wikanengsih; R. Mekar Ismayani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Poetry is a series of words and lines created by the expression of feelings and thoughts that make up a literary work. To beautify the language of a poem, the style of language used must be clear. Joko Pinurbo is an Indonesian writer who creates various poems. The poetry he creates has a unique language characteristic, is simple and has deep allusions. This study aims to examine the style of language used in the poems by Joko Pinurbo. The method in this research is descriptive qualitative with the type of literature study. The source of data used in this research is Joko Pinurbo's poetry library. The poems studied were entitled “Pacar Senja”, “Selepas Usia 60”, and “Tukang Potret Keliling”, which were analyzed based on the phrases and figures of speech contained in them. The study of poetry is carried out with semiotics, namely a way of studying a poem by enjoying its markers. The results of the review of the three titles of Joko Pinurbo's poems above, it is stated that the three works contain symbols and symbols that have a specific purpose. The use of diction in his poems is quite simple as it is often used in everyday life and has a good sense of humor.